A new genus of coral (Rugosa) from the Adarouch area (Brigantian, NE Central Morocco) - Said, Ismail; Rodríguez, Sergio (Coloquios de Paleontología, 2008)
A new genus of rugose coral, Tizraia, has been recorded in the Tizra and Akerchi formations of the Adarouch area (Brigantian, Central Meseta, Morocco). The new genus is characterised by incomplete, mesa-shaped tabulae, absence of axial structure and presence of well developed lonsdaleoid dissepiments, as well as parricidal increase. It evolved from Diphyphyllum by the development of lonsdaleoid dissepiments. Only the type species, Tizraia berkhlii gen. nov. sp. nov. is included with certainty in the new genus, but an additional species represented by one single specimen is tentatively described under this generic name. Tizraia has also been recorded in the Djerada Basin (Eastern Morocco) and may be present in Ireland. It has high biostratigraphic value as an Upper Brigantian (Upper Viséan) index taxon.